(untitled) (Research, Society and Development, 2022)
Obstetric violence is the term used to describe the various forms of violence that occur during pregnancy, childbirth, postpartum, and in abortion care. It can be manifested through physical, psychological, and verbal abuse, in addition to unnecessary interventional practices, such as episiotomy. Women in situations of social vulnerability and discrimination, such as black women, are more affected by obstetric violence. This article aimed to analyze the repercussions of obstetric violence to black brazilian women, based on literature studies. This is an integrative review, in which was used the PICO strategy and a validated instrument to guide the study in the databases of the Virtual Health Library, PubMed and Google Scholar, from papers published between 2011 and 2021. There was a selection of 06 articles after the inclusion and exclusion criteria. The studies showed that obstetric violence was more frequent in black women throughout the pregnancy-puerperal cycle, with the main repercussions being the unequal care and the negative consequences associated with mental health. The need for educational policies to denaturalize institutional racism and broaden the debate on racial inequities in health was perceived.